Evaluation of facilitators and barriers of timely breast cancer care in North Carolina (NC): A qualitative study. Issue 28 (1st October 2022) - Gaddy, Jacquelyne Janean; Teal, Randall; Bell, Emily Fox; Wheeler, Stephanie B.; Reeder-Hayes, Katherine Elizabeth
Abstract : 134 Background: Early detection and timely treatment of breast cancer using multi-disciplinary therapies often contributes to a goal of curative intent along with improved overall outcomes. In prior studies, Black women compared to non-Black women are at a higher chance of treatment delay (> 60 days) in NC. The care team factors that contribute to these treatment delays are unclear. Methods: This qualitative study utilized content analysis. The 30 participants included community stakeholders involved in breast cancer care delivery, including breast cancer clinicians and community resource providers. Participants were selected through purposive sampling. Three Area Health Education Centers (AHEC) regions (Northwest, Charlotte, and Area L) that represent the diversity of the state of NC were selected as sites for data collection. Each participant completed a one-time semi-structured interview which was audio-recorded and transcribed. Inductively derived codes were created from the previously established interview guide leading to the production of the codebook with each code conceptually defined. Transcripts were coded by 7 coders through the method of consensus coding leading to the identification of emergent themes. Code reports were generated from each code leading to the production of a narrative summary. Results: All participants identified perceived both facilitators and barriers to the timely initiation of breast cancer treatment. Barriers fell into several categories: geographical, financial, healthcare system related, and patient related (non-financial). Most barriers were perceived as more common among Black patients. Additionally, participants emphasized incidents of historical racism in medical care that limited Black patients from having trust in the healthcare system. Facilitators identified included: outreach through community partners, healthcare navigation, supportive healthcare providers, provision of social support services, transportation, integrative services, and raising the overall quality of cancer care. Conclusions: Despite the diversity of participants regarding region, years of employment, and role, stakeholders identified important common themes when reviewing the perceived facilitators and barriers of breast cancer care delivery. Perceived barriers were largely related to patients' social determinants of health, and participants perceived that Black patients had more adverse social determinants impacting their care timeliness, highlighting that structural racism contributes to delayed cancer care delivery. Future initiatives aimed at improving the delivery of timely breast cancer care must focus on evaluating marginalized communities' overall access to adequate care along with effective community engagement to build a higher level of trust from such patients and target the social determinants of health.